2022
DOI: 10.3390/children9081157
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Use of Quantitative Sensory Testing and Conditioned Pain Modulation and the Prescription of Medication and Interventional Procedures in Children with Chronic Pain Conditions

Abstract: The evidence supporting the use of pharmacological treatments in pediatric chronic pain is limited. Quantitative sensory testing (QST) and conditioned pain modulation evaluation (CPM) provide information on pain phenotype, which may help clinicians to tailor the treatment. This retrospective study aimed to evaluate the association between the use of QST/CPM phenotyping on the selection of the treatment for children with chronic pain conditions. We retrospectively analyzed the medical records of 208 female pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Moreover, the incidence of adverse effects is largely unknown. Clinicians can only follow what has been used in previous studies as well as the recommendations for treating adults and children [42]. Not surprisingly, almost all participants (99%) advocated evidence-based guidelines to support their daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the incidence of adverse effects is largely unknown. Clinicians can only follow what has been used in previous studies as well as the recommendations for treating adults and children [42]. Not surprisingly, almost all participants (99%) advocated evidence-based guidelines to support their daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the QST were available during the first evaluation and were used to personalize the treatment program of each patient. 13 , 14 …”
Section: Methodsmentioning
confidence: 99%
“…At the end of the evaluation, the diagnosis and personalized treatment plan (eg medications, physiotherapy, psychology, nursing, social worker, and interventional procedures) was discussed with the patients and their parents/caregivers. 13–18 Medication prescribed included non-steroidal anti-inflammatory drugs (eg ibuprofen, celecoxib), muscle relaxants (eg baclofen), opiates (eg morphine), anti-depressants (eg amitriptyline), anti-epileptics (eg gabapentin), anti-migraine agents, oral corticosteroids, sedatives (eg benzodiazepines), or other analgesics and antipyretics agents (eg acetaminophen, clonidine, magnesium, etc.). Interventional procedures included primarily peripheral nerve and interfascial plane single blocks, pulsed radiofrequency or local infiltrations.…”
Section: Methodsmentioning
confidence: 99%
“…107 Recent studies suggested that personalized treatment approaches to various pediatric chronic pain conditions in general, and in pediatric neuropathic pain in particular, can be developed based on the individual nociceptive phenotypes as determined by the use of Quantitative Sensory Testing and conditioned pain modulation evaluation (QST/CPM). [108][109][110] QST/CPM testing appears to provide more targeted therapeutic options, resulting in less polypharmacotherapy and the use of interventional treatments, while still being at least as effective as standard treatment protocols. However, further studies are needed to examine the potential benefits of pain phenotyping and to confirm these hypotheses.…”
Section: Brief Summary Of Pharmacologic and Non-pharmacologic Treatme...mentioning
confidence: 99%